Applying Paragraph Shrinking To Improve Grade II Students’ Reading Comprehension And Motivation In Learning English At Xyz School Jakarta - Lie Kartika Lesmana; M. B. Rini Wahyuningsih (Mathematics Education Study Program, 2025)
The low reading comprehension and learning motivation of Grade 2A students at XYZ Primary School in Jakarta served as the background for this study. The purpose of this research was to analyze the use of the paragraph shrinking strategy in improving the reading comprehension and motivation of Grade 2A students in English lessons. The study subjects were 17 Grade 2A students. The research method used was Classroom Action Research (CAR), consisting of three cycles. Each cycle included four stages: planning, implementation, observation, and reflection. Reading comprehension was measured using pre-tests and post-tests, while motivation was assessed using a rubric with four indicators. The research results have shown an increase in the average scores in the third cycle, with reading comprehension reaching 88.53 and motivation reaching 88.60. Based on these findings, it was concluded that the paragraph shrinking strategy can improve the reading comprehension and learning motivation of Grade 2A students in English at XYZ Primary School in Jakarta.